Requirement of Cavin-2 for the expression and stability of IRβ in adequate adipocyte differentiation - Yusuke Higuchi; Takehiro Ogata; Naohiko Nakanishi; Masahiro Nishi; Akira Sakamoto; Yumika Tsuji; Shinya Tomita; Satoaki Matoba (Elsevier, 2022)
Objective: Adipogenesis plays an essential role in maintaining energy and hormonal balance. Cavin-2, one of the caveolae-related proteins, is abundant in adipocytes, the leading site of adipogenesis. However, the details of the roles of Cavin-2 in adipogenesis remain unknown. Here, we demonstrate the requirement of Cavin-2 for the expression and stability of IRβ in adequate adipocyte differentiation. Methods: Cavin-2 knockout (Cavin-2 KO) and wild-type (WT) mice were fed with a high-fat diet (HFD) for 8 weeks. We evaluated body weight, food intake, and several tissues. Glucose homeostasis was assessed by glucose and insulin tolerance tests. Insulin signaling in epididymal white adipose tissue (eWAT) was determined by Akt phosphorylation. In vitro study, we evaluated adipocyte differentiation, adipogenesis-related genes, and insulin signaling to clarify the relationship between Cavin-2 and adipogenesis under the manipulation of Cavin-2 expression. Results: Caveolae structure decreased in eWAT of Cavin-2 KO mice and Cavin-2 knockdown 3T3-L1 cells. Cavin-2 enhanced the stability of insulin receptor (IR) through direct association at the plasma membrane in adipocytes, resulting in accelerated insulin/IR/Akt signaling-induced adipogenic gene expression in insulin-containing solution-stimulated 3T3-L1 adipocytes. IR-mediated Akt activation also enhanced Cavin-2 and IR expression. Cavin-2 knockout mice showed insulin resistance with dyslipidemia and pathological hypertrophic adipocytes after a HFD. Conclusions: Cavin-2 enhances IR stability through binding IR and regulates insulin signaling, promoting adequate adipocyte differentiation. Our findings highlight the pivotal role of Cavin-2 in adipogenesis and lipid metabolism, which may help to develop novel therapies for pathological obesity and adipogenic disorders.